Single-cell CRISPR screening characterizes transcriptional deregulation in T-cell acute lymphoblastic leukemia - Sarah Meyers; Olga Gielen; Jan Cools; Sofie Demeyer (Haematologica, 2024)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive type of leukemia caused by accumulation of multiple genetic alterations in T-cell progenitors. However, for many genes it remains unknown how their mutations contribute to disease development. Therefore, we performed two single-cell CRISPR screens in primary pro-T cells ex vivo to study the transcriptional impact of loss-of-function alterations in T-ALL and correlate this with effects on cell fitness. The various perturbations were clustered based on their effects on E2F/MYC or STAT/NOTCH signatures, which play a defining role in driving T-cell proliferation. Many of the perturbations resulted in positive effects on the STAT and NOTCH signatures and were predicted to behave as haploinsufficient tumor suppressors in T-ALL. Additionally, Spi1 was identified as an essential gene for pro-T cell survival, associated with deregulation of the MYC signature and epigenetic consequences. In contrast, Bcl11b was identified a strong tumor suppressor gene in immature T lymphocytes, associated with deregulation of NF-kB and JAK/STAT signaling. We found a correlation between BCL11B expression level and JAK/STAT pathway mutations in T-ALL patients and demonstrated oncogenic cooperation between Bcl11b inactivation and JAK3 hyperactivation in pro-T cells. Altogether, these single-cell CRISPR screens in pro-T cells provide fundamental insights in the mechanisms of transcriptional deregulation caused by genetic alterations in T-ALL.